2020
DOI: 10.1021/acs.jctc.9b00703
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Quantum Effects from the Analysis of Smoothed Trajectories: Pilot Study for Water

Abstract: Nuclear quantum effects have significant contributions to thermodynamic quantities and structural properties; furthermore, very expensive methods are necessary for their accurate computation. In most calculations, these effects, for instance, zero-point energies, are simply neglected or only taken into account within the quantum harmonic oscillator approximation. Herein, we present a new method, Generalized Smoothed Trajectory Analysis, to determine nuclear quantum effects from molecular dynamics simulations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 113 publications
1
32
0
Order By: Relevance
“…Recently we have shown that Berens' original idea about the quantum correction on thermodynamic properties can be extended to structural properties if the quantum correction is applied in time domain instead of frequency domain. 59,60 Our technique, the generalized smoothed trajectory analysis (GSTA) gives identical results for thermodynamics properties as 1PT+AC. For instance the heat capacity can be obtained from the VACF directly:…”
mentioning
confidence: 85%
“…Recently we have shown that Berens' original idea about the quantum correction on thermodynamic properties can be extended to structural properties if the quantum correction is applied in time domain instead of frequency domain. 59,60 Our technique, the generalized smoothed trajectory analysis (GSTA) gives identical results for thermodynamics properties as 1PT+AC. For instance the heat capacity can be obtained from the VACF directly:…”
mentioning
confidence: 85%
“…Recently we have shown that Berens' original idea about the quantum correction on thermodynamic properties can be extended to structural properties if the quantum correction is applied in time domain instead of frequency domain. 59,60 Our technique, the generalized smoothed trajectory analysis (GSTA) gives identical results for thermodynamics properties as 1PT+AC. For instance the heat capacity can be obtained from the VACF directly:…”
mentioning
confidence: 89%
“…62 In our previous study we showed that the 1PT+AC heat capacity can be significantly overestimated if the left Riemann sum is used instead of the trapezoidal rule in the computation of VDOS in eq 2. 59 To check whether this numerical error can occur in the calculation of the 2PT heat capacities, we tested thoroughly the "dos" analysis tool of the GRO-MACS that was used in ref 20. The default Fast Fourier Transformation routine in GROMACS applies the left Riemann rule but we also implemented a simple trapezoidal integral rule.…”
mentioning
confidence: 99%
“…The classical trajectories obtained this way include anharmonicity, however nuclear quantum effects need to be treated separately. This was done using the GSTA method 25 for which we give here a short summary.…”
Section: A Samplingmentioning
confidence: 99%
“…Recently a new method has been introduced to obtain quantum corrected trajectories and in turn quantum corrected structural properties and state functions such as heat capacities. 25 The method called Generalized Smoothed Trajectory Analysis (GSTA) is based on the idea that the quantum effects can be recovered from a classical trajectory by convoluting the classical coordinates with an appropriate weight function derived from the quantum harmonic partition function. It has been shown that quantum effects can be reproduced in a very efficient and cost-effective way.…”
Section: Introductionmentioning
confidence: 99%